Frequency of pain in Teeth with irreversible pulpitis after single visit root canal treatment using cryotherapy: intracanal cryotherapy - Junaid, Saman; Khan, Hanan Humayun; Bhangar, Faisal; Shah, Jawad Ali; Hussain, Syed Muzammil; Yousaf, Ajmal (Pakistan Armed Forces Medical Journal, 2023)
ABSTRACT Objective: To determine the frequency of pain in teeth with irreversible pulpitis after single visit root canal treatment using intra-canal cryotherapy.Study design: Quasi experimentalPlace and duration of study: Department of Operative Dentistry, Armed forces institute of Dentistry Rawalpindi from 1st June 2017 to 31st December 2017.Material and Methods: Total of 140 patients from 20 to 65 years were equally divided into two groups Group A in which Cryotherapy was used and Group B was control group. After anesthetizing the tooth & application of Rubber Dam, Root canal preparation was done with Protaper next series and copious irrigation of 5.25% sodium hypochlorite and 17% EDTA solution. In group A patients the final irrigation was done with Normal saline at a temperature of 2.5°C. In the control group, final irrigation was performed with normal saline at room temperature. Obturation was done with cold lateral condensation and permanent restoration was done with composite. Patients were contacted by telephone after 24 Hours and were asked whether they experienced any pain.Results: Mean age was 39.26+12.61 years. There were 82 (58.6) male and 58 (41.4) female patients. Comparison of cryotherapy group and controls was done in terms of post-operative pain. After 24 Hours 80% of the patients in group A has no pain while in control group 61.4% were pain free.Conclusion: Key words: Root canal treatment, cryotherapy, irreversible pulpitis, postoperative pain